PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK PADA PEMBELAJARAN AQIDAH AKHLAK UNTUK MENGEMBANGKAN KEMAMPUAN BERFIKIR KRITIS SISWA KELAS VIII DI MTS N 6 BOYOLALI - Waryanti, Zaroh Nisa; Rochmawan, Alfian Eko; Hidayah, Nur (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
This study aims to analyze the implementation of the project-based learning model (PjBL) in Aqidah and Akhlak subjects for eighth-grade students at MTs Negeri 6 Boyolali in the 2024/2025 academic year. The research focuses on enhancing students' critical thinking skills through an approach that promotes collaboration, problem-solving, and active learning. A qualitative descriptive method with a case study design was employed. Data were collected through interviews, observations, and documentation and analyzed using data reduction, data presentation, and conclusion drawing techniques. The results revealed that the project-based learning model positively impacted students' engagement and participation in Aqidah and Akhlak lessons. Students demonstrated a deeper understanding of religious concepts and their application in daily life. Supporting factors include adequate facilities, active roles of teachers as facilitators, and the development of activities aligned with students' needs. However, challenges such as students' lack of discipline in certain project activities and limited utilization of available facilities were also identified. This research implies that the implementation of project-based learning is an effective and innovative strategy to enhance students' critical thinking skills, especially in the context of Islamic religious education. Therefore, this model is recommended for broader integration into competency-based learning curricula.